Pengaruh Spiritual Emotional Freedom Technique (Seft) dan Murottal Surah Ar Rahman terhadap Kualitas Tidur Pasien Hemodialisa - Maya Ardilla Siregar; Ani Ramadhani Kaban; Yuliatil Adawiyah Harahap; Afina Muharani Saftriani (Poltekkes Kemenkes Jakarta III, 2023)
Hemodialysis has a negative effect on the psychological and physical patients so that in addition to causing hemodynamic disorders, patients will tend to experience sleep disorders. Poor sleep disorders will affect the quality of sleep and the healing process of the disease. As a nurse, nurses can provide nonpharmacological therapy in the form of a combination of relaxation and spiritual therapy, namely spiritual emotional freedom technique (SEFT) healing and listening to the Quran murottal surah Ar-Rahman. The purpose of this study was to analyze the effectiveness of the combination of SEFT and listening to the Quran murottal on the sleep quality of patients with hemodynamic disorders in the Hemodialysis room of RS Haji Medan. This study used quasi-experiments with onegroup pre-posts. The study was conducted on 35 patients in the hemodialysis room who had hemodynamic disorders with sampling techniques using purposive sampling. Intervention was carried out as many as 1 intervention for 1 cycle of SEFT and 30 minutes listening to the Quran murottal surah Ar Rahman using animated videos and headsets on patients after SEFT was carried out. Before and after the intervention, pretest and posttest were performed to assess the patient's sleep quality using the PSQI (Pittsburg Sleep Quality Sleep) questionnaire. Data analysis using SPSS with univariate analysis, bivariate analysis with t-paired t-test to analyze the effectiveness of the intervention. Result: Sleep quality improved before and after the intervention. Based on the paired t test, a p value of 0.000 is obtained. So that the combination of SEFT and listening to the Quran murottal is effective for the quality of sleep of patients with hemodynamic disorders in the hemodialysis room of RSU Haji Medan. The combination of Spiritual emotional freedom technique (SEFT) and listening to the murrottal of the Quran can improve the quality of sleep of patients with hemodynamic disorders in the hemodialysis room of RS Haji Medan.